Pengaruh PjBL terhadap Hasil Belajar Penulisan Artikel Ilmiah Populer melalui Proyek Majalah Digital Siswa Kelas VIII-6 SMPN 1 Pringgasela - Jumati - Rafida; Siti Rohana Hariana Intiana; Pipit Aprilia Susanti (Journal of Educational Review and Research, 2024)
This study aims to examine the effect of the Project-Based Learning (PjBL) model on the learning outcomes of Grade VIII-6 students at SMP Negeri 1 Pringgasela in writing populer scientific articles through a digital magazine project. In this model, students are artively involved in composing populer scientific articles based on appropriate structures anda language conventions, which are then integrated into a final product in the form of a digital magazine using online design applications. The study employed a quantitative approach with q pre-test and post-test design. Data were collected through assessments of the students written articles and the quality of the digital magazine they created in groups. The results indicate a significant improvement in students writing skills, particularly in aspects such as article structure, content accuracy, language clarity, and creativity. Furthermore, students collaboration and communication skills were enhanced throughout the magazine production process. These findings demonstate that implementing PjBL is not only effective in improving popular scientific writing skills but also fosters technological proficiency and teamwork in Indonesian language learning.